ANALISIS PEMANFAATAN TEMPAT TIDUR SELAMA MASA PANDEMI COVID-19 DI RUMAH SAKIT BAPTIS BATU - Soraya; Dony Kristian; Epa Dwi Harianti (JRMIK, 2023)
Background: Since it was declared a national disaster outbreak in April 2020, based on the official government website, namely Covid19.go.id, up to April 30, 2021, there have been 1,668,368 positive people for Covid-19, 1,522,634 recovered and 45,521 people died. These service changes include changes in the flow of patient admissions both outpatients and inpatients according to health protocols where patients are required to wear masks, through screening procedures, and restrictions on visitors / patient waiters and even separation of services for Covid-19 and Non-Covid-19 patients. With these changes, hospitals need to develop strategies that are obtained based on reports of hospital efficiency indicators for managing the resources needed to deal with the Covid-19 Pandemic.Objective : This study aims to analyze the inpatient efficiency indicators at Batu Baptist Hospital in 2020 with the Barber Johnson approach, to find out the policies and strategies carried out by Batu Baptist Hospital in order to achieve inpatient efficiency indicators according to the standards set during the Covid-19 Pandemic.Methods : The research was carried out at Batu Baptist Hospital on June 28, 2021 to July 31, 2021. The Method research used descriptive research with quantitative and qualitative approaches.Results : The results showed that during the Covid-19 pandemic, Batu Baptist Hospital made a policy regarding the criteria for accepting Covid-19 patients based on regulations set by the government. The policy was made to adjust the ability of Batu Baptist Hospital in providing services for Covid-19 cases. In addition, the management of the Batu Baptist Hospital also established a policy on the use of personal protective equipment (PPE), a policy for determining the Inpatient Installation (IRNA) room, a Covid-19 safety and control policy aimed at the safety of patients, staff and the community around the Batu Baptist Hospital. Inpatient efficiency indicators for the January – December 2020 period, of the 4 (four) inpatient efficiency indicators only 1 (one) indicator is in accordance with the Indonesian Ministry of Health standards namely BTO 50.08 times, while the other 3 (three) indicators are still not in accordance with Indonesian Ministry of Health standards, with the achievement of BOR 41.90%, ALOS 2.85 days, TOI 4.25 days.Conclusion : During the Covid-19 pandemic, the hospital's strategy to overcome the decline in patient visits due to Covid-19 was based on efficiency indicator reports, the hospital had a marketing strategy by prioritizing marketing digitalization by utilizing social media owned by Batu Baptist Hospital.Keywords : Analysis, Bed, Covid-19 Pandemic